Workplace Health Promotion as a good solution to the negative impact of the financial crisis on healthcare systems - Francesco Chirico (Journal of Health and Social Sciences)
The national healthcare systems of European countries were not immune to the impact of the recent global financial crisis. For instance, public expenditure on health in Ireland has fallen by about 9% since its peak in 2008, with consequences on the development of primary and community care [1]. In Greece, the recent austerity period imposed by the Troika has severely affected spending on healthcare services and the populations’ health has been referred to in the literature as ‘the Greek tragedy’ [2, 3]. While a systematic review on the impact of the 2008 financial crisis in Europe has shown heterogenous outcomes for health, there is consistent evidence linking economic crisis to mental health issues and the incidence of suicide [4]. The relationship between economic constraints, healthcare development and community health remains difficult to analyse, as the few and contested studies indicate [4]. Healthcare systems are frequently the first public services to suffer from government-imposed cuts, often prompting an increase in the commodification of healthcare. In this way, economics inequality becomes inequality in health standards. In Italy, recent data from the Italian National Institute of Statistics showed a disparity in life expectancy between the richer Northern and the poorer Southern regions of the country, a clear outcome of health inequality [5]. At the beginning of the century, the widespread Mediterranean diet, the favorable climate and the relaxed traditional lifestyle increased life expectancy for southern Italians, before growing factors, such as lower birthrates and worsening of economic resources, caused a trend inversion. In the same way, studies of the Essential Levels of Healthcare (LEAs) showed a dangerous worsening of public health provisions in several regions of the south of Italy [6]. Primary care, especially preventive medicine, has been one of the sectors most affected by the deterioration of healthcare standards, which is in turn the most effective strategies against some of the deadliest conditions affecting developed countries, such as cancer and cardiovascular diseases. An often-neglected solution to the lack of government funds for healthcare and preventive medicine is Workplace Health Promotion (WHP). The implementation of WHP programmes can improve employees’ lifestyles as well as the general standard of health of a community [7]. For instance, inexpensive campaigns against smoking, sedentary lifestyle and bad eating habits would create benefits at a public and at an occupational level. Indeed, lifestyle changes can increase fitness to work and decrease the likelihood of work-related diseases, while supporting the state’s efforts in preventive medicine and primary care. Additionally, targeted programmes implemented in the workplace have the ability to be far-reaching and extensive in their scope, influencing a wide range of working age adults and their families [8, 9]. As the worker’s health definition draws from WHO definition of health as “not only absence of disease, but presence of physical, psychological and social well-being”, strategies integrating the compulsory medical health surveillance and WHP programmes could create a cost-effective solution to benefit between the state, employers, workers and communities. However, governmental support, in the form of financial investment or tax advantages, is essential to integrate private investments from small and medium-sized enterprises and enhance WHP implementation. The right to a healthier workplace for the many can improve the health status level of all, especially the poorest with less access to healthcare services.